The Effect of Nurses' Psychological Climate Perceptions on Their Professionality in The Context of Work Engagement - Ülke Hilal Çelik; Atılhan Naktiyok (Asia Pacific Journal of Health Management)
Background: The psychological climate of the organization, the individual's perspective on work and whether they are engaged are meaningful in terms of the professionalism level of nurses. Because work engagement, as a concept completely opposite to burnout, refers to the emotional and motivational state of the employee towards his work.